Cultural and Ethical Effects on Managerial Decisions: Examined in a Throughput Model - Rodgers, Waymond (Journal of business ethics, 2001)
Financial and cost accounting information is processed by decision-makers guided by their particular need to support decisions. Recent technological advances impacting on information as well as organizations such as the European Community mandating financial reporting requirements for many countries is rapidly changing the landscape for decision making using accounting information. Hence, the importance of individuals' decision making is more important than it was previously. These decisions are also influenced by individuals' ethical beliefs. The Throughput Modeling approach to cultural and ethical concerns provides a way of dealing with accounting information processed through various pathways by decision-makers. This modeling approach captures different philosophical perspectives from which to understand what is involved in "thinking scientifically." In the Throughput Modeling approach, pathways highlight the importance of how different philosophical perspectives may be used by individuals in arriving at a decision. This paper highlights key concepts involved in rethinking the basis of moral decision making in terms of an underlying process, rather than focusing on the application of principles or the development of a virtuous character. Examples are provided from both English and Spanish settings to help emphasize the importance of modeling ethical decision making globally.